Method validation for the determination of 314 pesticide residues using tandem MS systems (GC–MS/MS and LC-MS/MS) in raisins: Focus on risk exposure assessment and respective processing factors in real samples (a pilot survey). (30th October 2021) - Constantinou, Maria; Louca-Christodoulou, Despo; Agapiou, Agapios
Highlights: A MRM analysis for 314 pesticides in raisins using tandem MS systems was performed. An ethyl acetate-based extraction method for pesticides in raisins was validated. Multiple residues pesticides were detected in the examined commercial samples. Processing factors and acute exposure assessment was applied in the analyzed raisins. Exposure assessment validity was based in real population data. Abstract: A multi-residue method for the simultaneous analysis of a wide range of pesticides in raisins using liquid and gas chromatography-tandem mass spectrometry (LC-MS/MS and GC–MS/MS) has been validated. Pesticides are extracted from raisins with ethyl acetate, followed by centrifugation. The validation study was in accordance with DG SANTE guidelines. Validation experiments have been performed in both analytical instruments. A total number of 314 pesticides were spiked in raisins of organic farming at two spiking levels for GC–MS/MS (0.025 and 0.1 mg/kg), and at three spiking levels for LC-MS/MS (0.005, 0.05, and 0.1 mg/kg) with 6 replicates at each concentration. The scope of validation included linearity, limits of quantification (LOQ), accuracy, precision, and matrix effects (%) for each pesticide. The validated method was then applied for the analysis of 37 commercial raisin samples purchased from the market. For the evaluation of the results, processing factors (PFs) have been applied to derive the amount of residue in raisins, from the maximum residue levels (MRLs) of grapes, and which in this paper will be referred as to the MRL expressed in raisins. In all conventional samples, pesticides were detected at concentrations above the LOQ. In total, 55 different pesticides were detected. All conventional samples contained multiple pesticides ranging from 2 to 24. On the other hand, samples from organic farming were found to be free of the analysed pesticides. The 13.5% of the examined samples were considered as violations. The exposure assessment for the acute risk of the violating samples indicated that no potential risk derives from the detected and approved in the EU pesticides, while the detection of not approved pesticides in the EU, and the lack of toxicological reference values for certain pesticides raise concerns for the human health, especially for children. The results of the survey study indicate the need to include processed samples, and in particular dry fruits with a high consumption rate such as raisins, in the official controls of pesticide residues in food.